2018
DOI: 10.3347/kjp.2018.56.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2, 6-Dichlorobenzonitrile on Amoebicidal Activity of Multipurpose Contact Lens Disinfecting Solutions

Abstract: Multipurpose contact lens disinfecting solutions (MPDS) are widely used to cleanse and disinfect microorganisms. However, disinfection efficacy of these MPDS against Acanthamoeba cyst remain insufficient. 2, 6-dichlorobenzonitrile (DCB), a cellulose synthesis inhibitor, is capable of increasing the amoebical effect against Acanthamoeba by inhibiting its encystation. In this study, we investigated the possibility of DCB as a disinfecting agent to improve the amoebicidal activity of MPDS against Acanthamoeba cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Finally, the biocides used in the OPTI-FREE products, namely, polyquaternium-1 and myristamidopropyl dimethylamine, have been shown to have the greatest efficacy against Acanthamoeba (and other ophthalmological pathogens) as compared with other biocides. [34][35][36] The results of the current investigation indicate similar results: products containing polyquaternium-1 and myristamidopropyl dimethylamine demonstrated significantly greater Acanthamoeba trophozoite disinfection efficacy than other biocides or combinations of biocides. According to the results demonstrated here, less effective biocides include polyaminopropyl biguanide or alexidine dihydrochloride combined with polyquaternium or polyquaternium-1.…”
Section: Wwwoptvisscicomsupporting
confidence: 71%
See 1 more Smart Citation
“…Finally, the biocides used in the OPTI-FREE products, namely, polyquaternium-1 and myristamidopropyl dimethylamine, have been shown to have the greatest efficacy against Acanthamoeba (and other ophthalmological pathogens) as compared with other biocides. [34][35][36] The results of the current investigation indicate similar results: products containing polyquaternium-1 and myristamidopropyl dimethylamine demonstrated significantly greater Acanthamoeba trophozoite disinfection efficacy than other biocides or combinations of biocides. According to the results demonstrated here, less effective biocides include polyaminopropyl biguanide or alexidine dihydrochloride combined with polyquaternium or polyquaternium-1.…”
Section: Wwwoptvisscicomsupporting
confidence: 71%
“…OPTI-FREE products have also previously been found to produce little or no encystment, 32,33 ensuring that the more vulnerable trophozoite form persists and is able to be acted upon by multipurpose solutions. Finally, the biocides used in the OPTI-FREE products, namely, polyquaternium-1 and myristamidopropyl dimethylamine, have been shown to have the greatest efficacy against Acanthamoeba (and other ophthalmological pathogens) as compared with other biocides 34–36 …”
Section: Discussionmentioning
confidence: 99%
“…The structure of the cyst contains a cellulose double wall with a fibrous laminar exocyst and a granular smooth endocyst. The composition of the cyst wall contains 1,4 b-glucan, also known as cellulose, 37 and other polysaccharides that make the wall more robust for protection. 38 After decades of storage, cysts can remain pathogenic and viable.…”
Section: Life Cycle Of Acanthamoebamentioning
confidence: 99%
“…They exert their effects by suppressing phospholipid biosynthesis, disruption of cellular membranes and intracellular signalling, and induction of apoptosis [30]. The herbicide 2,6-dichlorobenzonitrile inhibits cellulose synthesis and encystment of the amoeba [31]. The disinfectant povidone-iodine (PVP-I) has both trophicidal and cysticidal effects in vitro [32].…”
Section: Current Anti-acanthamoebic Therapymentioning
confidence: 99%
“…It works by damaging protein and nucleic acid synthesis [33]. In vitro study showed that at 0.5-2.5% PVP-I has a better activity on the trophozoite and cystic stages than CHX [31]. In vitro screening of derivatives of the heterocyclic compounds 1H-benzimidazole and 1H-benzotriazole, and their N-alkylated analogues against A. castellanii identified 5,6-dimethyl-1H-benzotriazole and 5,6-dibromo-1H-benzotriazole to be more cysticidal compared to CHX [34].…”
Section: Current Anti-acanthamoebic Therapymentioning
confidence: 99%